China's Higher Education on an Overpass of Four-Fold Transitions - Yiban, Wang (My University, 2007)
Through an analysis of graduate employment and the decline of quality and equity following dramatic enrollment expansion, Professor Wang of the University of Zhejiang will discuss the deep-seated conflicts facing higher education in China as it undergoes a major transition. This presentation is part of the "Ideas and Universities" International Video Seminar Series. Organized by scholars at the University of Bristol (UK), this series aims to find a shared language and offer a forum to examine past and present models of internationalization in higher education. Linked by distance technology, a diverse group of scholars and university leaders from around the world will explore key issues in higher education and globalization from current and historical perspectives.
Keywords: International and Comparative